Characterization and Expression Analysis of PtAGL24, a SHORT VEGETATIVE PHASE/AGAMOUS-LIKE 24 (SVP/AGL24)-Type MADS-Box Gene from Trifoliate Orange (Poncirus trifoliata L. Raf.) - Sun, Lei-Ming; Zhang, Jin-Zhi; Hu, Chun-Gen (Frontiers in Plant Science, 2016)
The transition from vegetative to reproductive growth in perennial woody plants does not occur until after several years of repeated seasonal changes and alternative growth. To better understand the molecular basis of flowering regulation in citrus, a MADS-box gene was isolated from trifoliate orange (precocious trifoliate orange, Poncirus trifoliata L. Raf.). Sequence alignment and phylogenetic analysis showed that the MADS-box gene is more closely related to the homologs of the AGAMOUS-LIKE 24 (AGL24) lineage than to any of the other MADS-box lineages known from Arabidopsis; it is named PtAGL24. Expression analysis indicated that PtAGL24 was widely expressed in the most organs of trifoliate orange, with the higher expression in mature flowers discovered by real-time PCR. Ectopic expression of PtAGL24 in wild-type Arabidopsis promoted early flowering and caused morphological changes in class I transgenic Arabidopsis. Yeast two-hybrid assay revealed that PtAGL24 interacted with Arabidopsis AtAGL24 and other partners of AtAGL24, suggesting that the abnormal morphology of PtAGL24 overexpression in transgenic Arabidopsis was likely due to the inappropriate interactions between exogenous and endogenous proteins. Also, PtAGL24 interacted with SUPPRESSOR OF OVEREXPRESSION OF CONSTANS1 (PtSOC1) and APETALA1 (PtAP1) of citrus. These results suggest that PtAGL24 may play an important role in the process of floral transition but may have diverse functions in citrus development.